The fertile ground of Hell's carnival: Charles T. R. Bohannan and the US Army's Counter Intelligence Corps' investigations of war criminals, collaborators, and the Huk, in the Philippines 1945–1947. Issue 1 (2nd January 2017) - Ridler, Jason
ABSTRACT: Insurgencies thrive in regions where government legitimacy is absent. In the post-war Philippines, Captain Charles T. R. Bohannan of the Army's Counter Intelligence Corps became actively aware of this dynamic. Bohannan is best known for his later work with Edward Lansdale and Ramon Magsaysay in defeating the Huk Rebellion (1950–1954). Here the author examines Bohannan's early investigative work against Japanese war criminals, wartime Filipino collaborators, and the rising threat of communist subversion most associated with the Huk. All of these experiences fed into what would be the successful campaign against the Huk, chronicled in his seminal work, Counter Guerrilla Operations: The Philippines Experience, and offers lessons on the investigative (as opposed to tactical or psychological) nature of effective counter-insurgency work, as it relates to both legitimacy in governance and the rise of insurgencies.